IMPLEMENTASI PENDIDIKAN INKLUSI DI TK DESA MRANGGEN 01 SUKOHARJO - Ayu Nur Khoyimah; Atina Khasanah; Umi Kultsum (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This research comes from combining normal children’s learning in reguler classes with children with special needs in reguler schools and are now able to attend regular schools. Children with special need who initially could only go to special schools and are know able to attended regular schools with an inclusive education system. The purpose of this study was o determine the aplication of inclusive education in TK Mranggen Village 01, the research method used was describtive qualitative. The Research subjects were children with special needs, school principals and class teachers as weel as TK Mranggen Village 01. Data collection using observation and intervie techniquest. Yhan the data obtained were analysed and conlusions were drawn about the data that had been collected. The result of this study are that TK Mranggen Village 01 every years accept children with special need but obstacle to date is the curriculum us in 2013 method and infrastructure to serve children with special needs, and the luck of experience and knowladge special teacher to handle children with special needs.Keywords: inclusive school; children with special need